2015
DOI: 10.1007/s11356-015-4505-8
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption-desorption reactions of two hazardous heavy metals in contaminated soils

Abstract: Investigating the interactions of heavy metals is imperative for sustaining environment and human health. Among those, Cd is toxic for organisms at any concentration. While Ni acts as a micronutrient at very low concentration but is hazardous toxic above certain threshold value. In this study, the chemical adsorption and desorption reactions of Ni and Cd in contaminated soils were investigated in both single and binary ion systems. Both Ni and Cd experimental data demonstrated Langmuir type adsorption. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Studies have widely reported that at certain pH, higher ionic strength is beneficial for the adsorption, while at other pH conditions, this effect may be reversed. Such a pH may be near the pHzpc (pH of zero point of charge) of the soil . For example, at pH greater than pHzpc, increasing ionic strength decreased Cd adsorption regardless of the soil type because the cations competed with Cd for the active adsorption sites . However, at pH higher than a certain level, increasing ionic strength increased the adsorption of As­(V), and vice versa .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have widely reported that at certain pH, higher ionic strength is beneficial for the adsorption, while at other pH conditions, this effect may be reversed. Such a pH may be near the pHzpc (pH of zero point of charge) of the soil . For example, at pH greater than pHzpc, increasing ionic strength decreased Cd adsorption regardless of the soil type because the cations competed with Cd for the active adsorption sites . However, at pH higher than a certain level, increasing ionic strength increased the adsorption of As­(V), and vice versa .…”
Section: Resultsmentioning
confidence: 99%
“…67 For example, at pH greater than pHzpc, increasing ionic strength decreased Cd adsorption regardless of the soil type because the cations competed with Cd for the active adsorption sites. 71 However, at pH higher than a certain level, increasing ionic strength increased the adsorption of As(V), and vice versa. 70 This is because the number of cations in the adsorption plane increases with increasing ionic strength, resulting in a less negative potential at the adsorption plane and thus facilitating the adsorption of As(V) by the soil.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The sediment contains more organic matter than the soil, so it has a stronger adsorption ability to nickel and a stronger fixation ability, leading to less desorption. Low Ni desorption may be the buffer of sediment and soil against heavy metal pollution ( Davari et al, 2015). The desorption process can be regarded as the reverse process of soil adsorption process, and all factors affecting adsorption affect the desorption.…”
Section: Figure 4 the Desorption Amount And Desorption Rate Of Ni In Soilmentioning
confidence: 99%
“…Contrarily, owing to their metal chelating functional groups, the organic desorbing agents were able to remove up to 90% of the adsorbed metals. Hence, either EDTA or DTPA could be utilized for regenerating the composite when applied for water purification (Ngah et al 2013;Davari et al 2015;Luo et al 2015). On the other hand, a lower desorption of adsorbed metals from the composite in the presence of Ca(NO3)2 makes the material suitable for immobilizing metals in contaminated soils where an environmental electrolyte concentration always exists.…”
Section: Distribution Coefficientsmentioning
confidence: 99%